1998
DOI: 10.1046/j.1365-2435.1998.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Close association of RGR, leaf and root morphology, seed mass and shade tolerance in seedlings of nine boreal tree species grown in high and low light

Abstract: 1. To test hypotheses concerning adaptation and acclimation of tree species to shaded habitats we determined the growth, biomass partitioning and morphology of seedlings of nine near‐boreal tree species in high‐ and low‐light greenhouse environment (25 and 5% of full sunlight, respectively), comparable to sunlit gap and shaded microsites in boreal forests. The species differ widely in shade tolerance, seed size and leaf life span. 2. In low light, all species allocated proportionally more biomass to stems and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
408
7
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 430 publications
(480 citation statements)
references
References 37 publications
(85 reference statements)
45
408
7
11
Order By: Relevance
“…Other responses presented by the plants under both shade conditions included lower R:S and higher LAR, LMR and SLA, with no distinct treatments differences between AS and NS. This growth pattern has been observed by others (Popma & Bongers 1988, 1991, Walters et al 1993, Osunkoya et al 1994, Reich et al 1998 and is considered an adaptation to shade. It is assumed that these responses taken together can increase the ratio of photosynthesis to respiration at the whole-plant level and contribute to the maintenance of a positive carbon balance and maximization of growth in shade (Kitajima 1994).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Other responses presented by the plants under both shade conditions included lower R:S and higher LAR, LMR and SLA, with no distinct treatments differences between AS and NS. This growth pattern has been observed by others (Popma & Bongers 1988, 1991, Walters et al 1993, Osunkoya et al 1994, Reich et al 1998 and is considered an adaptation to shade. It is assumed that these responses taken together can increase the ratio of photosynthesis to respiration at the whole-plant level and contribute to the maintenance of a positive carbon balance and maximization of growth in shade (Kitajima 1994).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, in contrast to other studies where lower SLA, LAR and LMR and higher R:S were observed for shadetolerant in comparison with shade-intolerant species (Rao & Singh 1989, Kitajima 1994, no consistent trend regarding successional positions was found. In a study with nine boreal tree species, Reich et al (1998) also failed to find any correlation between successional status and biomass allocation or LMR, yet they still observed significant correlations with respect to SLA and LAR. DeLucia et al (1998) also did not find any association of SLA and LAR with shade tolerance status.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations